Estudio de prevalencia de enfermedad renal crónica en pacientes hipertensos atendidos en una IPS de Montería. 2018 – 2020 (2021)
The present research work consists of identifying the prevalence of chronic kidney disease (CKD) in hypertensive patients who were treated at an IPS in the city of Montería between the years 2018 - 2020, through the analysis of variables that quantify the possibility of the development of CKD, in relation to non-modifiable risk factors (race, age, sex, and family history) and modifiable risk factors (obesity, overweight, salt and fat intake, sedentary lifestyle, smoking, and alcohol consumption). In the same way, the antihypertensive pharmacological therapies indicated in the studied population are analyzed, thus, in a quantifiable way, the different therapies are organized that will later display statistical data that will allow representing on average which of these have a greater use and relationship with the stage of the patients .